2011
DOI: 10.1007/s11431-011-4659-7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of flamelet model for supersonic turbulent combustion

Abstract: Being physically intuitionistic and computationally efficient, the flamelet model has obtained increasing attention and becomes popular in numerical simulations of supersonic combustion. However, the flamelet model was firstly built for simulations of the low-speed flows. Therefore it is still unclear whether the assumption of the flamelet model is reasonable in supersonic combustion. This paper tries to identify the existence of the flamelet mode in supersonic combustion. Firstly, the interaction of the turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The difference in the time and spatial scales of turbulent flow and chemical reactions determines the micro mixing and reaction process of the fuel, leading to different flame regimes. The turbulent chemistry interaction (TCI) in supersonic combustors depends not only on the flow condition, but also is affected by the fuel type [71,105]. In the Da (Damkohler number) -Re (Reynolds number) diagram shown in Fig.…”
Section: B Turbulent Combustion Model and Reduced Kerosene Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the time and spatial scales of turbulent flow and chemical reactions determines the micro mixing and reaction process of the fuel, leading to different flame regimes. The turbulent chemistry interaction (TCI) in supersonic combustors depends not only on the flow condition, but also is affected by the fuel type [71,105]. In the Da (Damkohler number) -Re (Reynolds number) diagram shown in Fig.…”
Section: B Turbulent Combustion Model and Reduced Kerosene Mechanismmentioning
confidence: 99%
“…Thus in scramjet combustors, the flame thickness may become smaller than the smallest turbulent eddies, which hence can only wrinkle the flame front to form corrugated flame rather than thicken the flame thickness through entering the reaction zone. For hydrogen fuels with small ignition delay time scale, experimental data and theoretical calculation show that most of the supersonic combustion region is in the regime of wrinkled laminar flames (Ki<1) or the upper regime of flamelets in eddies (1<Ka<100), where flamelet based turbulent combustion models are correct or approximately applicable [71,105]. Whereas for complex hydrocarbon fuels (e.g.…”
Section: B Turbulent Combustion Model and Reduced Kerosene Mechanismmentioning
confidence: 99%
“…Firstly, the oblique-shock compression caused by the inlet side wall and the strut makes the flow conditions of the air entering the combustor very different from free stream conditions, which produces uncertainty in the determination of the oxidizer boundary conditions in Equation (12). Secondly, the pressure in the combustion region will definitely differ from free stream pressure because of the inlet compression and the jet/cross-flow interaction.…”
Section: Combustion Casementioning
confidence: 99%
“…All of the numerical and theoretical studies by Bray et al [9], Balakrishnan and Williams [10], Gao and Lee [11] and Fan et al [12] indicated that the combustion processes inside the scramjet engine satisfy the flamelet assumption. Moreover, Waidmann et al [13] performed an analysis on the experimental data of a hydrogen-fuelled scramjet engine at the German Aerospace Centre (DLR) [9] and it was concluded that the combustion is in a flamelet mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation